BIOM-40. ANALYSIS OF SERUM MIRNA IN GLIOBLASTOMA PATIENTS: TARGETED ENRICHMENT OF EXTRACELLULAR VESICLES ENHANCES SPECIFICITY FOR PROGNOSTIC SIGNATURE. (9th November 2020) - Tzaridis, Theophilos; Weller, Johannes; Bachurski, Daniel; Schäfer, Niklas; Schaub, Christina; Hallek, Michael; Scheffler, Björn; Glas, Martin; Hartmann, Gunther; Herrlinger, Ulrich; Wild, Stefan; Coch, Christoph; et al.
Abstract: Glioblastoma is a devastating disease, for which biomarkers allowing a prediction of prognosis are urgently needed. microRNAs have been described as potentially valuable biomarkers in cancer. Here, we studied a panel of microRNAs in extracellular vesicles (EV) from the serum of glioblastoma patients and also in total serum without prior EV separation, and evaluated their correlation with the survival of these patients. Our study included 55 patients in total, 26 (47.3%) of which were treated within the multicenter Phase III CeTeG/NOA-09 trial and 29 (52.7%) in the Division of Clinical Neurooncology of the University Hospital of Bonn, as well as 10 healthy volunteers (HV). Blood was drawn from patients during the adjuvant chemotherapeutic treatment. A panel of 15 microRNAs was studied by quantitative real-time PCR in EV that were separated by size-exclusion chromatography, followed by CDxx* immunoprecipitation (SEC+CDxx*), and compared with those from total serum of glioblastoma patients and HV. Comparing SEC+CDxx* to total serum, we found evidence for enrichment of miR-21-3p and miR-106a-5p and, conversely, lower levels of miR-15b-3p in SEC+CDxx* EV. miR-15b-3p and miR-21-3p were upregulated in serum of glioblastoma patients compared to healthy subjects. Significant correlation with survival of the patients was found for levels of miR-15b-3p in total serum and miR-15b-3p, miR-21-3p, miR-106a-5p and miR-328-3p in SEC+CDxx* EV. Combining miR-15b-3p in serum or miR-106a-5p in SEC+CDxx* EV with any one of the other three microRNAs in SEC+CDxx* EV allowed for a prognostic stratification of glioblastoma patients. We have thus identified four microRNAs whose levels, in combination, can predict the prognosis for these patients. *=Cluster of Differentiation xx (CDxx); Molecule cannot be specifically mentioned due to pending patent.